Death in the freezer : - Vicary, Tim (Oxford Univ. Press, 1998)
Ellen Shore's family is an ordinary American family, but Ellen Shore is not happy when her brother Al is born, because her parents think that a son is more important than a daughter. Anh when she is an adult, she goes on hating him. She has three young kids, no husband, and very little money. But Al is rich. He is a famous rock star now, with lost of expensive cars, a beautiful big house, and a life of parties and travel. Ellen cleans his house, cooks for his parties, even steals drugs for him from the hospital whrere she works. Anh Al gives her nothing. So Ellen begins to make secret plans for her brother...